2006
DOI: 10.1128/jb.188.6.2115-2125.2006
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Biochemical Analysis of Starch Metabolism in the Hyperthermophilic Archaeon Pyrococcus furiosus

Abstract: Pyrococcus furiosus utilizes starch and its degradation products, such as maltose, as primary carbon sources, but the pathways by which these ␣-glucans are processed have yet to be defined. For example, its genome contains genes proposed to encode five amylolytic enzymes (including a cyclodextrin glucanotransferase [CGTase] and amylopullulanase), as well as two transporters for maltose and maltodextrins (Mal-I and Mal-II), and a range of intracellular enzymes have been purified that reportedly metabolize malto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
82
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 45 publications
2
82
2
Order By: Relevance
“…4H, we also found that Apu Tk plays a much greater role than expected in the cleavage of ␣-1,4-glycosidic linkages, suggesting that the experimentally verified ␣-amylase TK1884 protein (59) may not be the major amylose-degrading enzyme in T. kodakaraensis. This agrees well with the results of a transcriptome analysis of P. furiosus grown on starch, which revealed that PF1935*, the homolog of TK1774*, is the protein most up-regulated in the presence of starch (39).…”
Section: Discussionsupporting
confidence: 81%
“…4H, we also found that Apu Tk plays a much greater role than expected in the cleavage of ␣-1,4-glycosidic linkages, suggesting that the experimentally verified ␣-amylase TK1884 protein (59) may not be the major amylose-degrading enzyme in T. kodakaraensis. This agrees well with the results of a transcriptome analysis of P. furiosus grown on starch, which revealed that PF1935*, the homolog of TK1774*, is the protein most up-regulated in the presence of starch (39).…”
Section: Discussionsupporting
confidence: 81%
“…The enzymes involved in sucrose metabolism could not be identified from the genome sequence. No beta-fructofuranosidase (invertase) or sucrose phosphorylase could be identified, and there is no homolog of PF0132, which encodes the invertase purified from P. furiosus (27).…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, four enzyme activities have been detected in the family (18,46). The activities are ␣-amylase (22, 27), 4-␣-glucanotransferase (19,26,29,35), amylopullulanase (5,7,8), and ␣-galactosidase (43). The TK1436 protein was incubated at 70°C with melibiose, pullulan, maltoheptaose, or amylose as the substrate, and the reaction mixtures were analyzed by TLC (Fig.…”
Section: Identification Of Tk1436 As a Maltodextrin-induced Open Readmentioning
confidence: 99%